Pendampingan Lembaga PAUD Dalam Implementasi Metode Bermain Edukatif Islami Untuk Pembentukan Karakter Anak Usia Dini - Rahayu, Evi; Ramadhan, Syahri; Fernianti, Asri; Hutriani, Angga; Fitri, Widya; Gusrini, Heri (Al-Umm: Jurnal Pengabdian dan Pengembangan Masyarakat, 2024)
This community service activity aims to assist Early Childhood Education (PAUD) institutions in implementing Islamic educational play methods that are oriented towards character building in children from an early age. The assistance is provided through teacher training, the development of Islamic play activity kits, and direct practice with children. The methods used include observation, training, workshops, intensive mentoring, and evaluation. The results of the activity show an increase in teachers' understanding of Islamic educational play methods, the development of play activity kits integrated with Islamic values, and increased child involvement in activities that foster religious attitudes, discipline, cooperation, and responsibility. This program makes a real contribution to PAUD institutions in building children's character in a fun and age-appropriate way